Increased Dietary Leucine Reduces Doxorubicin-Associated Cardiac Dysfunction in Rats - Fidale, Thiago M.; Antunes, Hanna K. M.; Alex dos Santos, Luciano; Rodrigues de Souza, Fernanda; Deconte, Simone R.; Borges Rosa de Moura, Francyelle; Mantovani, Matheus M.; Alves Duarte, Poliana Rodrigues; Roever, Leonardo; Resende, Elmiro S. (Frontiers in Physiology, 2018)
Cardiotoxicity is one of the most significant adverse effects of the oncologic treatment with doxorubicin, which is responsible for a substantial morbid and mortality. The occurrence of heart failure with ventricular dysfunction may lead to severe cardiomyopathy and ultimately to death. Studies have focused on the effects of leucine supplementation as a strategy to minimize or revert the clinical condition of induced proteolysis by several clinical onsets. However, the impact of leucine supplementation in heart failure induced by doxorubicin is unknown. Therefore, the objective of this work is to evaluate the effects of leucine supplementation on the cardiotoxicity in the heart of rats treated with doxorubicin. Rats treated with a 7,5 mg/kg cumulative dose of doxorubicin for 14 days presented a dilatation of the left ventricle (LV), and a reduction of the ejection fraction (FE). The 5% supplementation of leucine in the rats´ food prevented the malfunctioning of the LV when administered with doxorubicin. Some alterations in the extracellular matrix remodeling were confirmed by the increase of collagen fibers in the doxorubicin group, which did not increase when the treatment was associated with leucine supplementation. Leucine attenuates heart failure in this experimental model with doxorubicin. Such protection is followed by the maintenance of interstitial collagen fibers.